2010
DOI: 10.1016/j.jcmg.2009.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pressure Recovery on Echocardiographic Assessment of Asymptomatic Aortic Stenosis: A SEAS Substudy

Abstract: For accurate assessment of AS severity, pressure recovery adjustment of AVA must be routinely performed. Estimation of pressure recovery at the sinotubular junction is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(142 citation statements)
references
References 30 publications
5
132
1
4
Order By: Relevance
“…15-17 These discrepancies may become larger in patients with a smaller diameter of the ascending aorta, and routine calculation of ELCo is recommended for assessing aortic stenosis in patients with aortic diameter <3 cm. 26 The difference in ELCoI was larger than the difference in EOAI, and this suggests the benefit of the Trifecta valve in patients with a small valve size.…”
Section: Regression Analysismentioning
confidence: 98%
“…15-17 These discrepancies may become larger in patients with a smaller diameter of the ascending aorta, and routine calculation of ELCo is recommended for assessing aortic stenosis in patients with aortic diameter <3 cm. 26 The difference in ELCoI was larger than the difference in EOAI, and this suggests the benefit of the Trifecta valve in patients with a small valve size.…”
Section: Regression Analysismentioning
confidence: 98%
“…6 In particular, AS severity is frequently overestimated by AVAI in patients with milder degree of AS if pressure recovery in the aortic root is not taken into account. 7 Recently, it was demonstrated that patients with inconsistently graded severe AS had a prognosis comparable to that seen in patients with moderate AS. 8 Whether assessment of pressure recovery adjusted AVAI (energy loss index [ELI]) in this setting could add accuracy to risk assessment is unknown.…”
mentioning
confidence: 99%
“…This difficulty may increase the possibility of over-or under-estimation of the AVA. In addition, although transvalvular pressure gradients are useful for the diagnosis of aortic stenosis, they might be overestimated when a pressure recovery phenomenon has occurred; 3,4) therefore, TTE including Doppler study is essential for the diagnosis of aortic stenosis, but it also has limitations. On the other hand, ECG-gated MDCT gives high resolution images and large amounts of information.…”
Section: Discussionmentioning
confidence: 99%
“…1) The surgical indication for SVD is wide according to functional valvular deterioration by Doppler study of transthoracic echocardiography (TTE). 3,4) The surgical procedure is almost always replacement. Thus, surgeons do not pay attention to the degree of valvular deformity.…”
Section: Introductionmentioning
confidence: 99%